Which one of the following logic expression is incorrect?
A.  1 ⊕ 0 = 1 
B.  1 ⊕ 1 ⊕ 0 = 1 
C.  1 ⊕ 1 ⊕ 1 = 1 
D.  1 ⊕ 1 = 0 
Option: B Explanation : Click on Discuss to view users comments. Mahvish said: (8:28am on Thursday 19th October 2017)
With the formulaA exOR B = A'B AB'

The circuit shown in the figure is equivalent to?
A. 

B. 

C. 

D. 

Option: B Explanation : Click on Discuss to view users comments. wdw said: (4:20pm on Monday 6th January 2014)
Please Explain how ?

The black box in the following figure consists of a minimum complexity circuit that uses only AND,OR and NOT gates. The function f (x,y,z) = 1 whenever x , y are different and 0 otherwise. In addition the 3 inputs x,y,z are never all the same value. Which of the following equation lead to the correct design for the minimum complexity circuit?
A.  x'y + xy' 
B.  x + y'z 
C.  x'y'z' + xy'z 
D.  xy + y'z + z' 
Option: A Explanation : Click on Discuss to view users comments. rehan said: (6:41pm on Saturday 28th February 2015)
A part not contain the value of Z so how it full fill the function ?????????

If A ⊕ B = C, then
A.  A ⊕ C = B 
B.  B ⊕ C = A 
C.  A ⊕ B ⊕ C = 0 
D.  Both (a) & (b) 
Option: D Explanation :
Mathematically, XOR is both associative and commutative ie.
If C = A XOR B then B = C XOR A or B = A XOR C and and A = B XOR C A = C XOR B Click on Discuss to view users comments. bikash said: (4:05am on Wednesday 4th September 2013)
Option C is also correct
bikash said: (4:05am on Wednesday 4th September 2013)
Option C is also correct

To make the following circuit a tautology ? marked box should be
A.  OR gate 
B.  AND gate 
C.  NAND gate 
D.  EXOR GATE 
Option: C Explanation : The output f = (x+x')+(y+y'). Starting derivation using 'f'. >(x+x')+(y+y') >(x+y)+(x'+y') >(Already a known Input)+(x'+y') So, the unknown input is (x'+y'). This can be made by : x and y fed into a NOT gate and then AND gate to become (x'+y'). So the answer is NAND gate. Click on Discuss to view users comments. swetha k said: (8:02pm on Monday 5th October 2015)
it should be XOR isn't it??
Sachin Raj G.S said: (10:23pm on Wednesday 4th April 2018)
C is the exact answer for this question. 1st input is x y2nd input will be x' y'(nand gate)Next there is a and gate, so output should become,f=(x y).(x' y') =xx' xy' yx' yy' =1 xy' yx' 1 =1(because 1 a=1)
